Citizenship Behavior among Kindergarten Children (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify citizenship behavior among kindergarten children. The researcher employed a descriptive approach with correlational relationships, which was deemed appropriate for achieving the research objectives. The research community was selected in an intentional manner, namely kindergarten children in the six Baghdad education directorates on both sides of Karkh and Rusafa. The total number of sample was 200 children chosen from 20 kindergartens. The results revealed that kindergarten students have a high level of citizenship. There is a significant difference between public and private kindergarten students regarding citizenship. There is no significant difference in citizenship behavior regarding students in kindergarten and preschool. There is no significant difference in citizenship behavior between male and female students. According to these results, the researcher recommended holding training courses, various activities, and workshops aimed at introducing teachers and educational supervisors in kindergartens to the importance of education for citizenship and its role in raising the awareness of community members about the importance of citizenship and providing them with the desired benefit. Setting up educational environments in kindergartens to teach topics of citizenship behavior by providing the necessary capabilities, tools, devices, and connections to the information network (Internet).